O-arm Imaging and Naviation Systems for Transvertebral Anterior Cervical Foraminotomy. Issue 1 (April 2016) - Umebayashi, Daisuke; Yamamoto, Yu; Nakajima, Yasuhiro; Hara, Masahito
Introduction: Anterior cervical discectomy and fusion (ACDF) results in excellent initial clinical results for herniated cervical disc and an osteophyte. On the other hand, the development of adjacent segment disease after ACDF is well recognized. However, most patients do not require total discectomy and vertebral fusion because most radiculopathies are caused by focal lesions of the intervertebral foramen. Especially, in patients who have unilateral radiculopathy with physiological alignment, we should avoid removal of healthy discs. Transvertebral anterior cervical foraminotomy (TVACF), nonfusion and nondiscectomy technique, can preserve intervertebral disc and reduce adjacent intervertebral degeneration compared with intervertebral fusion. Therefore, we have reported the advantages and usefulness of TVACF. However, TVACF requires skillfulness, especially for the appropriate drilling direction control for the keyhole. Recently, O-arm imaging and navigation systems were progressed. This navigation systems help to make the correct direction of the keyhole. Material and Methods: We have performed TVACF under O-arm imaging and naviation systems. The patient was placed in the supine position. A lateral radiograph was used to identify the skin incision level. A 3.5cm transverse skin incision was made at half a level higher than the affected disc level. We approached the anterior surface of the vertebra from the affected side. After then, O-arm imaging and navigation systems were applied. We determined the appropriate keyhole position under the navigation. The lateral and caudal side trajectory of the tunnel was also decided under the navigation. The tunnel was 6 mm in diameter. Results: Under O-arm imaging and navigation systems, we were able to easily determine the appropriate keyhole position and the lateral and caudal side trajectory of the tunnel. Intraoperative findings and postoperative computed tomography imaging showed the accuracy of keyhole position. Conclusion: Successful surgery is possible with using O-arm imaging and navigation systems. This navigation facilitate TVACF. As a result, TVACF is able to be more widely used among spinal surgeons in safe.